A National Survey on Mental Health Professional Development in Juvenile Justice Facilities: Implications for Youth Reentry. (May 2021) - Gagnon, Joseph Calvin; Swank, Jacqueline M.
A national study of clinical directors examined professional development (PD) focused on mental health provided to professionals in juvenile justice facilities for adjudicated youth. A total of 85 clinical directors responded to a mail survey (45% return rate). The survey questions related to (a) topics of staff training and the basis for choosing topics, (b) which professionals participated in each PD topic, (c) training format and frequency of PD, (d) recommended attributes of PD, (e) methods of evaluating PD, and (f) adequacy of PD and how can it be improved. For each topic, PD was typically provided once per year and face to face, rather than online. PD participation rates were commonly in the 30% and 40% ranges for professionals other than clinical directors and counselors, with teachers, correctional officers, administrators, and teaching assistants receiving PD the least. Rarely did PD include recommended attributes of PD, and it was commonly viewed as ineffective. Implications for research and practice related to PD and its relationship to youth reentry from juvenile justice facilities are discussed.